Systematic literature review of the role of e-commerce in providing pathways to sustainability for poverty alleviation in Sub-Saharan Africa - Cordes, D.L.; Marinova, Dora (2023)
Poverty elimination by 2030 is the major initiative of the United Nations Sustainable Development Goals. However, poverty in Sub-Saharan Africa is rising. There is an absence of structural reform for transformational change across the region. E-commerce is an enabler of small and large businesses in developed economies. Community-led initiatives for poverty alleviation may benefit from the transactional capabilities of e-commerce for direct trade with suppliers and consumers. Well-structured small and medium-size enterprises (SMEs) can foster local innovation and entrepreneurship, and collaboration between SMEs can enhance product development and marketing strategies. This review aims to discover formal research into the application of e-commerce in sustainable development models for poverty alleviation in Sub-Saharan Africa, and the extent of innovation, entrepreneurship, and collaboration among SMEs. The review found an absence of formal research into theories and practical strategies for sustainability innovations across the low-income spectrum. Organizational structures have not been developed to stimulate outreach, to foster innovation and entrepreneurship, or to embrace technology. Further, there is limited discussion on the importance of collaboration for the sharing of knowledge and joint business activities, but there is acknowledgement that SMEs can provide spatially diversified sustainable development. This article proposes a framework for the implementation and management of networks of SMEs focused on the sustainable development of low-income communities.